Tingkat Pengembalian Investasi Pendidikan di Kalimantan Barat Tahun 2018 - Ayu, Sakuntala Devi; Mulatsih, Sri; Novianti, Tanti (UI Scholars Hub, 2021)
Theoretically, human capital plays an important role in economic growth. In West Kalimantan, the government increase the education investment to improve human capital. This study aims to estimate the rate of return of education investment in West Kalimantan Province, Pontianak and Singkawang District. SAKERNAS 2018 individual data was analyzed using the Mincer Model and the Heckman’s Two-step procedure. The result show that the rate of return of education investment in West Kalimantan province is 3,83 percent. It means that each additional year of schooling will increase income by 3,83 percent. The rate of return of education investment in Pontianak and Singkawang District are 6,21 percent and 4,87 percent, respectively.